Analysis on Malaysian consumers acceptance towards purchasing organic banana / Ainnur Haziqah Mohd Noh - Mohd Noh, Ainnur Haziqah (Faculty of Plantation and Agrotechnology, 2019)
Organic banana is one of the nutritional foods and it is good for health. Eating organic banana may add additional health benefits as compare to eating non-organic banana. Organic banana contain less synthetic fertilizer, artificial colouring, flavouring, sweeteners and preservations, some of it may be harmful for human body. The study was conducted to identify the determinants or factor that influenced the consumer’s acceptance towards organic banana in Malaysia. The survey method was used for data collection. The questionnaires were distributed to 52 respondents that consists of consumer in Malaysia. The random sampling technique was used in this survey. The results were interpreted by factor analysis by using Statistical Package for Science Computer Software (SPSS) version 23. There were three independent variables for the studies which were price, knowledge and environmental concern. The result from the factor analysis based on the KMO’s value showed that 0.582 which was moderate. The KMO’s value greater than 0.5 was considered acceptable. From the total variance explained, price factor was dominant attribute represented by three factors which were eigenvalues more than 1. The factors were willing to pay extra (4.476), suitable price (2.388) and interested to buy (1.776). It showed that 61.715% of the variance would be explained by the factors. . Based on the rotated table, there are 7 item that influenced in factor 1 and 5 of the factors were price. It can be explained that price factor is the most dominant factor. Other than that, in factor 2, there were 4 item that being extracted and 3 of the factors are represented knowledge. Then, in factor 3 there were 3 item that being extracted and it represent environmental concern. Thus, it can be concluded that price was most dominant factor on Malaysian consumer’s acceptance towards purchasing organic banana.